PARTNERSHIP IN OPEN INNOVATIONS – EXPERIENCE FROM THE AGRICULTURAL MARKET: POLAND CASE STUDY - Zenon Pokojski (Polityki Europejskie, Finanse i Marketing)
The ability to build and manage a knowledge transfer partnership is one of the most highly demanded skills. Knowledge is widely dispersed, so it should be acquired from the environment. For this purpose, partnerships should be established with different entities. Presumably, the most mature type of partnership is the innovation ecosystem. Hence empirical research was conducted among Poland’s Grupa Azoty (GA) Puławy's consortium members based on an in-depth, partially structured interview, supported by an analysis of several innovation ecosystems of chemical companies. The aim of the research was to assess the phenomenon of open innovations in the GA along with the characteristics of the selection of partners, cooperation strategies and declared resources for jointly implemented projects.